Global prevalence and subgroup analyses of coronavirus disease (COVID‐19) associated Candida auris infections (CACa): A systematic review and meta‐analysis. Issue 7 (25th May 2022) - Vaseghi, Narges; Sharifisooraki, Joobin; Khodadadi, Hossein; Nami, Sanam; Safari, Fatemeh; Ahangarkani, Fatemeh; Meis, Jacques F.; Badali, Hamid; Morovati, Hamid
Abstract: Background: Increased hospitalisation rates in the Coronavirus disease 19 (COVID‐19) era lead to a new wave of hospital‐acquired infections such as emerging multidrug‐resistant Candida auris . We aimed to evaluate and estimate the global prevalence of coronavirus‐associated C. auris infection (CACa). Methods: We searched related databases between December 2019 and April 2022 for studies that reported data about CACa. Meta‐analysis was performed using MedCalc software version 20.104 according to the DerSimonian and Laird method applying the random‐effects model. We evaluated heterogeneity using the χ 2 ‐based Q statistic (significant for p ‐value < .1) and the I 2 statistic (>75% indicative of 'notable' heterogeneity). Moreover, if possible, an odds ratio (OR) analysis was performed for eligible data. Results: Our meta‐analysis includes ten eligible studies, including 1942 patients hospitalised with COVID‐19; 129 were C. auris cases. The overall pooled prevalence of CACa was estimated at 5.7%. The mortality rate of CACa was estimated at 67.849%. Hypertension was the most prevalent comorbidity (59.374%), followed by diabetes mellitus (52.898%) and cardiovascular diseases (31.392%). Men with a prevalence rate of 80.012% were 3.27 (OR) times more prone to getting infected by C. auris . Conclusion: We concluded that the prevalence of C. auris infections decreased during the COVID‐19 pandemic and the prevalence gradient changed from Asia to America. Unfortunately, there are many descriptive studies with duplicate content in the field of epidemiology of C. auris infections which are increasing every day. We suggest further non‐descriptive studies to accurately establish the cause‐and‐effect relationships between C. auris and COVID‐19 infections.